1998
DOI: 10.1007/s002960050056
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in juvenile systemic lupus erythematosus: a longitudinal study on the effect of steroids on bone mineral density

Abstract: Peak bone mass is an important determinant of future bone mass and of the risk of osteoporosis and subsequent fractures. Although some information concerning bone mineral density (BMD) in adults affected with systemic lupus erythematosus (SLE) is available, few data on children and adolescents have been reported. Many variables, such as duration and activity of the disease, reduced sun exposure, and steroid therapy have been suggested as risk factors in the pathogenesis of osteoporosis in SLE. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
87
2
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 21 publications
12
87
2
2
Order By: Relevance
“…Two previous studies in juvenile SLE showed that BMD was correlated with cumulative corticosteroid dose, but the study populations included adults with childhood-onset SLE, as well as children (2,14). Consistent with our findings are the results of studies in adult premenopausal patients with SLE, in which decreased BMD was not found to be correlated with corticosteroid use, total corticosteroid dose, or duration of corticosteroid use (29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Two previous studies in juvenile SLE showed that BMD was correlated with cumulative corticosteroid dose, but the study populations included adults with childhood-onset SLE, as well as children (2,14). Consistent with our findings are the results of studies in adult premenopausal patients with SLE, in which decreased BMD was not found to be correlated with corticosteroid use, total corticosteroid dose, or duration of corticosteroid use (29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 82%
“…The major difference between our study and previous investigations in juvenile SLE is that the sample size of pediatric patients in our study was larger than those in the earlier studies in which lower BMD in patients with juvenile SLE was also demonstrated (14,16). Consistent with our results were the findings of 2 studies of patients who were Ͼ19 years old at the time of study but whose SLE had begun during childhood, both of which demonstrated decreased BMD (2,14). While the frequency of osteopenia was comparable (14), the frequency of osteo- Disease duration (0.0028), lupus nephritis (0.0541) Correlation with hip BMD Ͻ80% Disease duration (0.0249) * Three separate multivariate analyses using 2 of 3 interrelated variables at a time were performed.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations